QUO VADIS INVASI SEKUTU TERHADAP LIBYA - HARINI, SETYASIH (Transformasi, 2010)
Abstract This article explores about the reason why US and NATO attack Libya. Libya is one of the maghribi country that received an impact of democratic movement after Tunisia and Egypt. That democratic movements want Gadhaffi hold a general election to elect new government and free life from dictator government. Libya under Gadhaffi never held a general election and in fact he changed a system of government according to himself. Gadhaffi who hold his power more than 42 years against a tide of popular support for fresh voices. For US and his alliance make the reason behind the Libyan military strike is not only the traditional justification of protecting the national interest.Â It can called right to protect, is an effort to create a new international moral standard to prevent violence against civilians after more than six thousand people had accidently killed. Gadhaffi also failed to make a demokratic country. Issue about democratic country is very significant and important for Western Countries. They can do everything to rebuilt a democratic country according to they will. But it can be denied that Libya's oil reserves, as large as they are. Oil is very significant and it is the real national interest for US and its alliances. Keywords: power, attack, oil, human right, democratic country